2016
DOI: 10.1016/j.celrep.2016.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Selective In Vitro Propagation of Nephron Progenitors Derived from Embryos and Pluripotent Stem Cells

Abstract: Nephron progenitors in the embryonic kidney propagate while generating differentiated nephrons. However, in mice, the progenitors terminally differentiate shortly after birth. Here, we report a method for selectively expanding nephron progenitors in vitro in an undifferentiated state. Combinatorial and concentration-dependent stimulation with LIF, FGF2/9, BMP7, and a WNT agonist is critical for expansion. The purified progenitors proliferated beyond the physiological limits observed in vivo, both for cell numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 41 publications
5
97
0
Order By: Relevance
“…2) and the Six2 expression patterns in the Notch LOF and GOF mutant kidneys (Figs 3 and 4) provide compelling evidence to support the idea that Notch signaling downregulates Six2. Consistent with this, it was recently shown that pharmacological inhibition of Notch signaling promotes self-renewal of Six2 + nephron progenitors in vitro (Tanigawa et al, 2016; Yuri et al, 2015). Expression of Six2 appears to be regulated by multiple factors.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…2) and the Six2 expression patterns in the Notch LOF and GOF mutant kidneys (Figs 3 and 4) provide compelling evidence to support the idea that Notch signaling downregulates Six2. Consistent with this, it was recently shown that pharmacological inhibition of Notch signaling promotes self-renewal of Six2 + nephron progenitors in vitro (Tanigawa et al, 2016; Yuri et al, 2015). Expression of Six2 appears to be regulated by multiple factors.…”
Section: Discussionsupporting
confidence: 63%
“…Since treatment of nephron progenitors with a GSK inhibitor causes repression of Six2, we concluded that β-catenin contributes to the repression of Six2. However, it was recently reported that Wnt/β-catenin signaling is required for the maintenance of nephron progenitors in vivo and in vitro (Brown et al, 2015; Karner et al, 2011; Tanigawa et al, 2016). A low level of β-catenin might be required for the maintenance of Six2 expression and a high level of β-catenin might contribute to the downregulation of Six2.…”
Section: Discussionmentioning
confidence: 99%
“…In recent works by Brown et al [24], Tanigawa et al [25] and Li et al [26], hPSC-derived NPCs have only reported limited expansion under specific culture conditions that have increased the propagation of primary murine [24][25][26], rat [25] and human NPCs [26]. Thus, culture conditions for longterm expansion of hPSC-derived NPCs remain still unknown.…”
Section: Generating Kidney Organoids From Hpscsmentioning
confidence: 99%
“…By recapitulating the signalling the environment of NPCs, Brown et al [24] developed specific culture conditions that enabled the in vitro expansion of murine NPCs up to 10 passages [24]. In another study, Tanigawa et al [25] could propagate mouse or rat NPCs for 5 passages using a different protocol. More recently, Li et al [26] successfully derived mouse and human NPC lines reporting long-term propagation for more than 110 and 50 passages, respectively, under specific 3D culture conditions.…”
Section: Generating Kidney Organoids From Hpscsmentioning
confidence: 99%
“…Moving to the kidney, Ryuichi Nishinakamura (Kumamoto University, Japan) discussed his latest efforts in generating 3D kidney organoids, which he showed could form nephron-like structures complete with glomerular podocytes and proper vasculature when transplanted. He also showed how to expand nephron progenitors from mouse embryos and human iPSCs in vitro, generating a number that should be sufficient for future regenerative medicine (Tanigawa et al, 2016). Finally, Nori Tsumaki (CiRA, Japan) explained how iPSCs could be used to produce chondrocytes that generate hyaline cartilage rather than fibrous cartilage, which is unlike current cell therapies for cartilage (Yamashita et al, 2015).…”
Section: Cell Differentiation and Disease Modelingmentioning
confidence: 99%